Clearing and sanitization of media used for digital storage: towards recommendations for secure deleting of digital files - Golubić, Kruno (Array, 2012)
Simply deleting files with tools that are shipped with operating system isn’t good option if security and privacy are primary goals. To achieve secure deletion of digital files specialized tools or software must be used. Methods that are used differ from one case to another depending on goals that need to be accomplished – whether media will be reused or disposed. At the moment there is no public recommendation in Croatia how should one treat these security challenges. Certain institutions and organizations have their own internal procedures and security policies that are available only on the “need to know” basis. Therefore, the authors provide pointers to the publicly available documents from other countries, which one could use for creation of its own polices and rules. This is an on-going process that should follow advancing trends in technology.